Extropy estimation of Weibull distribution under upper records - Nour El Houda Zouaoui (The Journal of Engineering and Exact Sciences)
Recently, extropy has gained interest by the academic researchers. This work explores the features of parametric and non-parametric estimators based on upper record values under the a two-parameter Weibull distribution. We apply the Markov Chain Monte Carlo (MCMC) method to provide a Bayesian estimator. A considerable number of theoretical properties of the procedures are determined.